Equivalence in the Translation of Joko Pinurbo’s “Tuhan Datang Malam Ini” into “God Came Tonight” - Aurelia Reza Hayuwardhani (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2020)
The paper presents an analysis of Joko Pinurbo’s “Tuhan Datang Malam Ini” translated into “God Came Tonight”. In this paper, the translation of the original version is seen closely to see its equivalence strategies, referring to Nida’s framework, applied to the production of the translation. The equivalence explained in the discussion covers both formal and dynamic. The discussion in the paper leads to three major conclusions, namely: (1) figurativeness in a poem can be preserved by the help of formal equivalence, (2) the type of equivalence depends on how far translators bring it to the translation, and (3) translators need to have broad knowledge to supply their work in translation, especially in that of poetry.